Human and Nature in Physical Education and Health: A Diffractive Analysis of Policy Documents - Karin Isaksson; Erik Backman (Australian Journal of Environmental Education)
The research field of physical education and health (PEH) holds a great potential for exploring environmental issues, but the interest has been scarce. In this paper, we aim to trouble the separation of humans and nature, which has long been reproduced in PEH research and practice. To frame the problem, we turn to environmental education (EE) research, where scholars have argued that the human/nature divide serves as a foundation for environmental degradation. Drawing on Karen Barad’s posthumanist framework of agential realism, we explore the emerging conceptualisations of humans and nature when Swedish PEH policy documents are diffractively read through previous research, the concept of agential cuts and our own historicities. The analysis is presented through three diffraction patterns emerging around movement, health and indoors/outdoors, phenomena which are central not only to PEH but also to EE. We conclude that thinking with diffraction can open spaces within PEH educational policy for reimagining existing binaries between humans and nature. In this way, PEH practice might contribute to troubling the foundations for environmental injustices and issues of unsustainability.